Differences in Knowledge, Attitudes, and Practices of Complementary Feeding Before and After Nutrition Education with Video Media for Baduta Mothers at Posyandu Mawar 03 & 04 West Pademangan, North Jakarta - Putri, Maulida Nugrah Priadi; Marbun, Rosmida Magdalena (Politeknik Kesehatan Kemenkes Jakarta II, 2024)
Nutritional issues are prevalent among children under the age of five in Indonesia, particularly among those aged 6-23 months. This is due to several factors, including early complementary feeding and a lack of variation in each meal. To determine the differences in knowledge, attitudes, and practices of complementary feeding before and after nutrition education with video media for baduta mothers at Posyandu Mawar 03 & 04 West Pademangan, North Jakarta. This study was Pre-Experimental using a One Group Pre-Test Post-Test Design with Purposive Sampling, obtained 40 respondents. The Chi-Square test and the Wilcoxon Matched Pairs test were used to analyze the data. There was a relationship between maternal education with attitudes and practices of complementary feeding before nutrition education through video media. There were differences in knowledge, attitudes, and practices of complementary feeding before and after nutrition education with video media for baduta mothers at Posyandu Mawar 03 & 04 West Pademangan, North Jakarta. Video could be used as an alternative media used in complementary feeding nutrition education to see differences in knowledge, attitudes, and practices of baduta mothers providing complementary feeding.